Functional fillers : chemical composition, morphology, performance, applications - Wypych, George (ChemTec Publishing, 2018)
"Fillers do not fill but modify the next generation materials, control their properties, open new applications. This opening sentence underlines the aims of this book which shows applications of fillers resulting from their chemical composition (or modification) and/or special morphological features. This combination results in a high performance required by many new products. The book has two sections: analysis of the most current modifications in respect of the chemical composition and morphology of classical fillers (some of the over 100 fillers listed in Handbook of Fillers, 4th Edition) which contributed to the exceptional enhancements in their properties and applications."--